PEMBELAJARAN KONSTRUKTIVISTIK UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA SMA - Santoso, Handoko (UNIVERSITAS MUHAMMADIYAH METRO, 2010)
The purpose of this research is to know the influence of biology through constructivistic learning towards the critical thinking ability. This research addresses the role of constructivistic learning (inquiry and cooperative learning strategy) as well as these interactions towards the increase of the critical thinking ability. Quasy experimental research of Pretest-postest nonequivalent control group design with factorial design 2x2x2 were implemented on X grade student of the state SMA in Metro City Lampung. The research sample consists of 96 students. To examine hypothesis, it is used Ancova technique and continued by LSD test. There was a difference on the critical thinking ability between students who learn by inquiry level 1 with student who learn by inquiry level 2. and there was not difference on the critical thinking ability between students who learn by STAD cooperative with student who learn by TPS. There is no effect of interaction between inquiry with cooperative towards the critical thinking ability. Kata kunci: konstuktivistik, kemampuan berpikir kritis